2019
DOI: 10.1039/c9ra06527j
|View full text |Cite
|
Sign up to set email alerts
|

Nifuroxazide ameliorates lipid and glucose metabolism in palmitate-induced HepG2 cells

Abstract: Inflammation constitutes an important component of non-alcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Intracellular lipid accumulation was determined by Oil Red O staining using a previously reported method with slight modifications [ 16 ]. HepG2 cells were plated in a 96-well plate at a density of 1×10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular lipid accumulation was determined by Oil Red O staining using a previously reported method with slight modifications [ 16 ]. HepG2 cells were plated in a 96-well plate at a density of 1×10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…It can be seen that insulin-resistant HepG2 cells showed the increased relative mRNA expression level of PCK-1 and G6PC even in the presence of 100 nM insulin (Figure ). These results indicated that the gluconeogenesis rate increased in IR-HepG2 cells due to the blockage of the insulin pathway axis by palmitate, TNF-alpha, and fructose . Treatment of IR-HepG2 cells with GPCK-1 showed nearly 70% downregulation of the PCK-1 gene as compared to the untreated IR cells as shown in Figure A.…”
Section: Resultsmentioning
confidence: 74%
“…These results indicated that the gluconeogenesis rate increased in IR-HepG2 cells due to the blockage of the insulin pathway axis by palmitate, TNF-alpha, and fructose. 38 Treatment of IR-HepG2 cells with GPCK-1 showed nearly 70% downregulation of the PCK-1 gene as compared to the untreated IR cells as shown in Figure 6A. Treatment with EPCK-1 (EscortIV: PCK-1 siRNA(10 nM) conjugate) as a positive control also showed a similar level of downregulation in the PCK-1 gene (0.82 ± 0.20), indicating that the effective delivery and knockdown of the target gene were achieved by our synthesized nanoformulation (0.76 ± 0.28).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To induce fatty liver conditions, we treated HepG2 and SNU-449 cells with PA, a free fatty acid. PA-treated hepatocytes have been used in previous studies as a fatty liver model to simulate lipid accumulation and IR (Xiao et al 2019;Gao et al 2010;Liu et al 2019;Zhang et al 2019). As shown in Figs.…”
Section: Discussionmentioning
confidence: 99%